Maritime challenges and priorities in Asia : implications for regional security - Ho, Joshua.; Bateman, W. S. G. (Routledge security in Asia Pacific series ;, 2012)
"Maritime issues are particularly important for Asian countries, where there is a high reliance on shipping routes for international trade, many difficult disputes over maritime boundaries, and the prospect of increasing tensions where maritime power might play a significant role. This book provides a comprehensive survey of the maritime issues affecting Asia."--Publisher's description.